2019
DOI: 10.1111/ejn.14553
|View full text |Cite
|
Sign up to set email alerts
|

Axonal projection‐specific differences in somatodendritic α2 autoreceptor function in locus coeruleus neurons

Abstract: The locus coeruleus (LC) contains the majority of central noradrenergic neurons sending wide projections throughout the entire CNS. The LC is considered to be essential for multiple key brain functions including arousal, attention and adaptive stress responses as well as higher cognitive functions and memory. Electrophysiological studies of LC neurons have identified several characteristic functional features such as low‐frequency pacemaker activity with broad action potentials, transient high‐frequency burst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 37 publications
4
21
0
Order By: Relevance
“…In particular, the ER was larger in right dominant subjects. Since noradrenergic ascending projections are mainly ipsilateral ( Berridge and Waterhouse, 2003 ; Wagner-Altendorf et al, 2019 ), this finding could be related to a larger noradrenergic tone impinging on the right hemisphere ( Kruglikov et al, 1992 ), dominant for those spatial skills ( Joseph, 1988 ) required in the matrices test. An excessive level of basal noradrenergic activity is in fact detrimental for performance, according to the “adaptive gain theory” proposed by Aston-Jones and Cohen (2005) .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the ER was larger in right dominant subjects. Since noradrenergic ascending projections are mainly ipsilateral ( Berridge and Waterhouse, 2003 ; Wagner-Altendorf et al, 2019 ), this finding could be related to a larger noradrenergic tone impinging on the right hemisphere ( Kruglikov et al, 1992 ), dominant for those spatial skills ( Joseph, 1988 ) required in the matrices test. An excessive level of basal noradrenergic activity is in fact detrimental for performance, according to the “adaptive gain theory” proposed by Aston-Jones and Cohen (2005) .…”
Section: Discussionmentioning
confidence: 99%
“…Though both cell types are dispersed throughout the LC, the small fusiform cells dominate the densely packed rostral portion, indicating a cytoarchitectonic bias [145]. In addition, recent studies have indicated phenotypic variability among subsets of LC neurons [17,124,165]. Hippocampal and prefrontal-innervating LC neurons differ in their physiological response to the α 2 -adrenoreceptor agonist clonidine, suggesting a functional heterogeneity within the LC neuron population [165].…”
Section: Neuroanatomy and Function Of The Locus Coeruleusmentioning
confidence: 99%
“…In addition, recent studies have indicated phenotypic variability among subsets of LC neurons [17,124,165]. Hippocampal and prefrontal-innervating LC neurons differ in their physiological response to the α 2 -adrenoreceptor agonist clonidine, suggesting a functional heterogeneity within the LC neuron population [165].…”
Section: Neuroanatomy and Function Of The Locus Coeruleusmentioning
confidence: 99%
“…In addition to the bilateral relationship between LC and HIPP, according to Mello-Carpes et al findings, the LC-HIPP-NTSparagigantocellularis (PGi) pathway can significantly affect recognition memory performance [31]. Furthermore, the frontal cortex-LC pathway is another modulator of this memory through α2adrenoceptor signaling [32]. Based on the abovementioned reports, it can be concluded that the neurological activity of locus coeruleus and its noradrenergic projections to different brain areas, like the HIPP, play a pivotal role in the development of this higher function memory (Figure 3) [29].…”
Section: Lc and Recognition Memorymentioning
confidence: 97%